Dyeing and antibacterial activation with methylene blue of a cyclodextrin modified polyester vascular graft. Issue 9 (1st October 2013) - Kacem, I.; Laurent, T.; Blanchemain, N.; Neut, C.; Chai, F.; Haulon, S.; Hildebrand, H. F.; Martel, B.
Abstract The aim of this study was to develop an antiseptic and blue dyed polyester (PET) vascular graft in order to reach two distinct properties: (i) the prevention of postoperative infections, (ii) the improvement of the graft compatibility with the coelioscopy surgical technique. This work consisted of dyeing a vascular prosthesis with methylene blue (MB) which is known as a cationic dye with antiseptic properties. Therefore, the functionalization of the PET fibers of the prosthesis with a cyclodextrin–citric acid polymer (PolyCD) was achieved in order to improve its sorption capacity. The NMR experiments demonstrated that a 1:2 complex occurred between hydroxypropyl β‐cyclodextrin (HP‐βCD) and MB. Kinetic and sorption isotherm studies showed that an impregnation of the polyCD modified prosthesis (PET‐CD) in a 1 g L−1 of MB solution for 150 min was sufficient to reach the saturation of the device. Results proved that the adsorption mechanism followed the Langmuir model and a maximum of 20 mg g−1 of MB on the graft. A sustained release of MB in batch tests was observed in PBS and in vitro microbiological assays displayed a prolongation of the bactericidal effect of PET‐CD whose extent varied with the amount of MB preliminarily adsorbed onto the PET‐CD. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2942–2951, 2014.